Behavioural Insights in Traffic Congestion Mitigation in the Special Region of Yogyakarta: Analysis and Modelling of Driver Decision-Making - Fauzan Yoga Pratama; Mutiara Dicinta (Journal of Industrial Engineering and Halal Industries, 2026)
Traffic congestion in the Special Region of Yogyakarta (DIY) is a complex problem characterised by mixed traffic and manual interactions between road users. This study aims to formulate a conceptual model extending the Theory of Planned Behaviour (TPB) to identify the psychological determinants influencing road users' decisions regarding traffic congestion mitigation in DIY. The original TPB model was extended by adding the variables Perceived Cost and Perceived Usefulness. A quantitative approach was adopted through the distribution of a questionnaire survey to drivers in DIY, with the collected data subsequently analysed using structural equation modelling (SEM). The results of the structural model analysis indicate that this model extension successfully explains 56.1% of the variance in drivers’ intentions (R² = 0.561) and 45.0% of the variance in actual congestion mitigation behaviour (R² = 0.450). Of the seven constructs tested, four factors were found to have a significant influence on drivers’ decisions: subjective norms, perceived costs, perceived usefulness, and driving intention. Conversely, the constructs of attitude and perceived behavioural control were found to have no significant influence on the intention to mitigate congestion. The main conclusion of this study indicates that decision-making by motorists in DIY is more likely to be driven by moral values (social pressure) and rationality (cost calculations and perceived usefulness) than by personal attitudes or situational control. The practical implications of this study can be utilized by the Regional Government in DIY to design transport intervention policies based on behavioural insights, such as optimising public transport fare incentives and social norm campaigns.